A Pictorial Review of Cranial Nerves Imaging Anatomy and Pathology: Part 2—Pathology. (30th September 2022) - Kulkarni, Ashwini; Tiwana, Muhammad Hamza; Sobieh, Ahmed; Qayati, Mohamed; Abbassy, Ahmed; Dubey, Prachi; Abayazeed, Aly
Abstract : Cranial nerve pathology can range from the neoplasm, inflammation, infection, vascular, autoimmune, injury, and developmental abnormalities to anatomic variations. Involvement of cranial nerve can have a significant functional impact on the patient ranging from denervation, sensory, and motor deficits to autonomic abnormalities. Identification of common cranial nerve pathology is essential in adequately understanding basis of clinical presentation and guiding further management and follow-up. In this article, we present a summary of common pathologies affecting cranial nerves.